2021
DOI: 10.1007/s40122-021-00321-5
|View full text |Cite
|
Sign up to set email alerts
|

Historical Review of Studies on Sacroiliac Fatty Nodules (Recently Termed “Back Mice”) as a Potential Cause of Low Back Pain

Abstract: Low back pain is a widespread and poorly understood condition that is frequently diagnosed as non-specific low back pain. We were intrigued by the presence of painful sacroiliac nodules in patients with this condition. We conducted a historical review to elucidate this relationship. This chronicled review summarizes the overlooked literature from different countries, especially from around the 1950s, regarding the diagnosis and management of these painful nodules. Biopsies have confirmed the adipose nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In a study performed by Bicket et al [6], among ambulatory patients with low back pain who seek treatment, estimates of back mice ranged from 33% to 58%, highlighting the incidence of this condition in the general population. A narrative review performed by Canis Parera et al in 2016 [5] reported the clinical signs commonly observed in the literature regarding episacroiliac lipomas. The clinical presentation described in the study matches that of the patients included in this case series, including nodule presence, chronology of symptoms, pain characteristics, palpation, referred pain patterns, as well as aggravating and relieving factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study performed by Bicket et al [6], among ambulatory patients with low back pain who seek treatment, estimates of back mice ranged from 33% to 58%, highlighting the incidence of this condition in the general population. A narrative review performed by Canis Parera et al in 2016 [5] reported the clinical signs commonly observed in the literature regarding episacroiliac lipomas. The clinical presentation described in the study matches that of the patients included in this case series, including nodule presence, chronology of symptoms, pain characteristics, palpation, referred pain patterns, as well as aggravating and relieving factors.…”
Section: Discussionmentioning
confidence: 99%
“…Episacroiliac lipomas, also known as "back mice", "sacroiliac fatty nodules", and "iliac crest pain syndrome" may be an undetected cause of non-specific LBP with a high incidence in the general population. These lipomas, as the name suggests, are deeply tethered masses of fatty tissue that seem to herniate from deep fat pads located at the lumbosacral spine [5]. They are usually located at the site of the sacroiliac joint but can also be found around the lumbar spine or the iliac crest [5].…”
Section: Background and Purposementioning
confidence: 99%
See 2 more Smart Citations